Macro-economic variables and financing decisions of Nepalese non-financial firms (The International Research Journal of Management Science, 2022)
Purpose - The purpose of this paper is to examine the macro-economic indicators and firm characteristics that impact the financing decision of the Nepalese enterprises.Methodology - To evaluate the fundamental issues related to firm-specific variables on financing decision of Nepalese enterprises, the study used descriptive, and causal comparative research designs. The study used secondary data from 19 enterprises from 2001 to 2019 listed in NEPSE.Findings - The findings show that liquidity, inflation, profitability, growth opportunity, and gross domestic product are the major indicators for leverage measures. More specifically, it is found that firm size is more statistically significant for total debt financing, suggesting that firms with greater assets or turnover likely to have easier access to borrowing more fund from the capital market.Implication: As the linkage between growth opportunity and short-term debt is significant and negative implies that growth upsurges cost of financial distress, decreases free cash flow problems, and intensifies debt related issues. Thus, it is advised to the managers to use less debt and place larger value on stakeholder co-investment. Further, the finding also suggests that firms should employ less debt during the time of inflationary trend in the economy as inflation shows negative indication to debt financing.Limitations: The scope and sample size are the primary limitation of this study. The study comprises only non-financial firms of the NEPSE base listed firms. It also limits to secondary data analysis. Primary survey may produce recent scenario of the enterprises that they face in their financing decision.Originality/value: One field of study is believed to be the unique paradigm of macro-level indicators impacting leverage. The second is a piece of work that attempts to compare the results based on both the ratio of long-term to short-term debt and the total amount of overall debt.